Implementasi Kode Etik Jurnalistik dalam Penulisan Berita Kriminal di TribunBanten.com - Putri, Ariesa Amanda; Mukarom, Zaenal; Bahrudin, Bahrudin (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this writing is to find out the application of the journalistic code of ethics in writing criminal news on the online media TribunBanten.com, especially articles 4 and 5. The method used in this study is a case study which will explore data by means of a detailed analysis of the completeness of the background and has the aim of interpreting the interrelationships between the variables. The results of this study indicate that TribunBanten.com has not fully implemented the journalistic code of ethics articles 4 and 5 on murder crime news because several violations have been found in them. The existence of these violations has an impact on several aspects, such as the level of news objectivity and low news value to form the image of unprofessional journalists in the public eye.